Analytical optimization of intermediate band systems: Achieving the best of two worlds. (6th June 2018) - Suchet, Daniel; Delamarre, Amaury; Cavassilas, Nicolas; Jehl, Zacharie; Okada, Yoshitaka; Sugiyama, Masakazu; Guillemoles, Jean‐Francois
Abstract: Lagrange multipliers provide a powerful framework to devise the optimization of systems under constraints. It can be especially useful in the context of photovoltaics, where electrical or structural continuity relations impose connections between quantities, such as current matching between the different subcells of tandem devices. In this work, we apply this method to Intermediate band solar cell, an advanced concept for solar energy conversion in which 2 low‐energy photons can promote an electron to the conduction band through a so‐called intermediate band . We demonstrate that an intermediate band solar cell under solar spectrum cannot meet voltage preservation and current matching at the same time. By contrast, we show that the implementation of an energy shift ( electronic ratchet ) in any of the bands lifts one of the constraints set on the system and allows those 2 criteria to be filled simultaneously. Additional insights are provided by the numerical study of the short‐circuit current and fill factor of the systems at stake, which show that a system with ratchet benefits from the same current increase as a standard intermediate band solar cell (same short‐circuit current), while maintaining I‐V properties of a single junction (same open‐voltage circuit, same fill factor). Abstract : Using Lagrange multipliers, we study analytically the role of the electronic ratchet in Intermediate Band Solar Cells. The ratchet enables the system to preserve voltage while matching currents transiting through the intermediate band. This allows the system to benefit from the same current increase as a standard IBSC, while keeping the same open‐circuit voltage and fill‐factor as a standard single junction.